2013
DOI: 10.2174/1874306401307010046
|View full text |Cite
|
Sign up to set email alerts
|

Adult Rat Bone Marrow-Derived Stem Cells Promote Late Fetal Type II Cell Differentiation in a Co-Culture Model

Abstract: Bronchopulmonary dysplasia develops in preterm infants due to a combination of lung immaturity and lung injury. Cultured pluripotent bone marrow stem cells (BMSC) are known to reduce injury and induce repair in adult and in immature lungs, possibly through paracrine secretion of soluble factors. The paracrine relationship between BMSC and primary fetal lung epithelial type II cells is unknown. We determined the effects of BMSC on type II cell and fibroblast behavior using an in vitro co-culture model. Rat BMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
(80 reference statements)
2
7
0
Order By: Relevance
“…We speculate that the pneumocyte-like phenotype of ATII-LCs could progress further to full differentiation upon immersion into a more complete lung environment, either in the tissue in vivo or in more elaborated cell culture models that could incorporate features like the presence of an air-liquid interface. In this sense, Transwell devices have been reported as successful for lung differentiation by other groups [24] , [26] , and it could provide additional signaling to improve full differentiation of ATII-LCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that the pneumocyte-like phenotype of ATII-LCs could progress further to full differentiation upon immersion into a more complete lung environment, either in the tissue in vivo or in more elaborated cell culture models that could incorporate features like the presence of an air-liquid interface. In this sense, Transwell devices have been reported as successful for lung differentiation by other groups [24] , [26] , and it could provide additional signaling to improve full differentiation of ATII-LCs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, administration of MSCs from different origins into animal models of lung injury has been demonstrated by a number of authors to be a valuable therapeutic tool [24] , [26] , [63] [68] . We have recently reported that DMSCs could be useful for future clinical applications [33] , [69] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows an overview of the different types of models as well as sources from which cells and tissue are commonly derived. These include 2D cultured cells or 3D-organotypic lung co-cultures as well as ex vivo anatomical scaffolds or models derived from live tissue or 3D-printed using biomimetic materials ( Sucre et al, 2020 ; Montigaud et al, 2019 ; Möbius et al, 2018 ; Jiang et al, 2018 ; Leeman et al, 2019 ; Montemurro et al, 2006 ; Sucre et al, 2018 ; Knoll et al, 2013 ). Fetal primary epithelial cells isolated from human or rodent lung tissues can be cultured together with lung-derived fibroblasts or MSCs to study the effect of hyperoxia regarding the expression of transcription factors associated with pulmonary development.…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…In summary, in vitro models meet the need to reduce the use of animals in research, and provide an easily accessible platform in which to dissect the currently less understood molecular consequences of hyperoxia and to screen candidate therapeutics for treatment of BPD ( Wu et al, 2018 ; Leeman et al, 2019 ; Knoll et al, 2013 ). Knowledge gained from these customizable models will allow investigators to manipulate developmental pathways within the lung, in order to improve clinical outcomes associated with BPD.…”
Section: In Vitro Modelsmentioning
confidence: 99%